Composing Well‐Defined Stimulus‐Responsive Materials Through Postpolymerization Modification Reactions. Issue 9 (2nd April 2014) - Roth, Peter J.
<x xml:space="preserve">Abstract</x> Postpolymerization modification—the installation of functional groups into a premade, reactive polymeric precursor—is emerging as an advantageous synthetic strategy toward tailored materials. In this article, the preparation of environmentally sensitive, "smart, " polymers by virtue of postpolymerization modification is presented. The underlying fundamentals of different types of stimulus‐responsiveness are highlighted with an emphasis on thermoresponsiveness, encompassing lower and upper critical solution temperature (LCST and UCST) behavior. Using a range of postpolymerization modifications as examples, properties imparted through incorporation of specific functional groups and their structure–property relations are discussed. Strategies for an appropriate choice of functionality in order to obtain well‐defined materials with custom‐made behavior are presented. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>